PENGEMBANGAN SISTEM INFORMASI KEPEGAWAIAN BERBASIS WEB PADA MAN 1 PADANG - Rendy Harisca; Asrul Huda; Legiman Slamet (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2017)
Information Systems serve as a tool for managing palayanan in the organization to be more accurate, effective and efficient. In MAN 1 Padang TU Head is still difficult to manage employee data because there is no database management that can store, process, and maintain the integrity of personnel data. To improve the service in MAN 1 Padang is in need Civil Service Information System-based web that is able to manage personnel services, from employee data input process, employee leave process, employee mutation process and employee retirement process are mutually integrated as a whole.          This design is implemented with PHP programming language with MySQL database and CodeIgniter framework. In the system design involved Use Case diagrams, Activity diagrams, Context Diagrams, flowmap, Normalization and Entitiy Relationship Diagram. This system involves 3 users ie Employee, Admin, and Principal. The three levels of registered users have a private account to enter into the system ie username and password for the admin and principal while the employee enters by using NIP and Password with MD5 encryption.          This personnel information system produces web-based applications that can help Administrative Officers in improving the effectiveness and efficiency in the implementation of personnel management activities as well as displaying actual information in the form of employee data reports, employee pension information, history of employee mutation and employee leave history. Keywords: Human Resources Information System, PHP, MySQL database,                    CodeIgniter framework.